The Effectiveness of the Implementation of Diversion for Children of Criminal Offenders in Ternate City - Namikotomo, Bondan (Majapahit Journal of Islamic Finance and Management, 2025)
This study aims to analyze the effectiveness of diversion implementation for juvenile offenders in Ternate City and recommend penal and non-penal policy reforms in criminal law. The research method combines normative and empirical legal approaches, utilizing interviews, observations, and document analysis of cases handled by the Ternate Police. Findings indicate that diversion has reduced stigmatization through restorative mechanisms, yet its effectiveness is hindered by law enforcers’ limited understanding, inadequate facilities, and public resistance to restorative justice. Case studies, such as recidivism by offender Isra Nasrun, highlight the need for post-diversion mentoring evaluation. Legal reform recommendations include officer training, public education, and integrating non-penal policies focused on social rehabilitation. The study concludes that multidisciplinary collaboration is essential to strengthen diversion implementation and ensure child rights protection is aligned with the best interests of the child principle.